Jerusalem icons in the European space. - Kuhnel, B. (Peeters Publishers, 2022)
Based on scripture, exegesis, and an ongoing dialogue with the Jewish and Islamic presence, Jerusalem maintains a central position in Christian spirituality. After several studies that mapped visual references to the holy city in various other representational media, Bianca Kühnel dedicates the present volume to the monumental presence of Jerusalem in European Latin Christianity. The works discussed in this book have a spatial dimension, defined by mimetic architecture and mimetic topography brought to life by ritual movement. They consist of the reproductions of key buildings representing Jerusalem?s most sacred sites, standing alone or arranged in clusters. Jerusalem sites throughout the world challenge the usual notions of transfer and representation in the history of art by their number, their variety of means, and their level of historical consistency. This book traces key turning points in the long history of Jerusalem abroad, while defining a common methodological and theoretical framework.